2009
DOI: 10.2298/aoo0902007p
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei and chromosomal aberrations in healthy tobacco chewers and controls: A study from Gujarat, India

Abstract: Background: Tobacco chewing is attributed to oral cancer. Prediction of cancer development by genotoxicity analysis is a major challenge to identify tobacco users at greater risk. Therefore, present study aimed to analyze tobacco related genotoxic effects in chewers monitoring micronuclei (MN) and chromosome aberrations (CA). The biomarkers were compared with non chewer to (i) predict risk for genotoxicity, (ii) estimate synergistic effect of tobacco exposure with level of biomarkers, and (iii) identify best c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
(22 reference statements)
4
16
0
Order By: Relevance
“…Hence, MN assay can be used as a biomarker of genotoxicity. This study was also in accordance with the previous studies conducted by Patel et al [19] and Palaskar and Jindal, [20] who observed that the score of the MN frequency decreased as we moved from the SLT chewers to the smokers and then to the non-users and the non-smokers. A study carried out by Sardas et al [21] states that the oral use of SLT represents a genotoxic hazard, which is even higher than the DNA damage observed in cigarette smokers.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, MN assay can be used as a biomarker of genotoxicity. This study was also in accordance with the previous studies conducted by Patel et al [19] and Palaskar and Jindal, [20] who observed that the score of the MN frequency decreased as we moved from the SLT chewers to the smokers and then to the non-users and the non-smokers. A study carried out by Sardas et al [21] states that the oral use of SLT represents a genotoxic hazard, which is even higher than the DNA damage observed in cigarette smokers.…”
Section: Discussionsupporting
confidence: 93%
“…As the groups were for their mean difference, it was statistically significant (P < 0.05). This finding was with accordance with the study done by Palaskar and Jindal, [12] Patel et al, [13] and Bansal et al [1] …”
Section: Discussionsupporting
confidence: 92%
“…The result showed that the overall level of mean number of micronuclei in smokeless tobacco were higher (24.13 ± 10.68) as compared with smokers (11.96 ± 4.23) and controls (4.17 ± 2.99). This observation was similar to those reported by Palaskar et al .,[3] Ozkul et al ,[9] and Patel et al ,[10] when all the groups were further compared with each other for the mean difference, the result was highly statistically significant ( P < 0.05), which was in accordance with the previous studies by Palaskar et al . [3] and Patel et al .,[10] whereas Ozkul et al found no difference between the mean percentage of MN cells for the groups considered ( P > 0.05).…”
Section: Discussionsupporting
confidence: 93%